Genomic characterization of chronic lymphocytic leukemia (CLL) in radiation-exposed Chornobyl cleanup workers - Juhi Ojha; Iryna Dyagil; Stuart C. Finch; Robert F. Reiss; Adam J. de Smith; Semira Gonseth; Mi Zhou; Helen M. Hansen; Amy L. Sherborne; Jean Nakamura; Paige M. Bracci; Nataliya Gudzenko; et al. (BMC, 2018)
Abstract Background Chronic lymphocytic leukemia (CLL) was the predominant leukemia in a recent study of Chornobyl cleanup workers from Ukraine exposed to radiation (UR-CLL). Radiation risks of CLL significantly increased with increasing bone marrow radiation doses. Current analysis aimed to clarify whether the increased risks were due to radiation or to genetic mutations in the Ukrainian population. Methods A detailed characterization of the genomic landscape was performed in a unique sample of 16 UR-CLL patients and age- and sex-matched unexposed general population Ukrainian-CLL (UN-CLL) and Western-CLL (W-CLL) patients (n = 28 and 100, respectively). Results Mutations in telomere-maintenance pathway genes POT1 and ATM were more frequent in UR-CLL compared to UN-CLL and W-CLL (both p < 0.05). No significant enrichment in copy-number abnormalities at del13q14, del11q, del17p or trisomy12 was identified in UR-CLL compared to other groups. Type of work performed in the Chornobyl zone, age at exposure and at diagnosis, calendar time, and Rai stage were significant predictors of total genetic lesions (all p < 0.05). Tumor telomere length was significantly longer in UR-CLL than in UN-CLL (p = 0.009) and was associated with the POT1 mutation and survival. Conclusions No significant enrichment in copy-number abnormalities at CLL-associated genes was identified in UR-CLL compared to other groups. The novel associations between radiation exposure, telomere maintenance and CLL prognosis identified in this unique case series provide suggestive, though limited data and merit further investigation.